Theological imagination as hermeneutical device: Exploring the hermeneutical contribution of an imaginal engagement with the text - Viljoen, Anneke (HTS teologiese studies, 2016)
In the past, biblical scholarship has neglected the hermeneutical contribution that an imaginal engagement with the text may make. The author’s aim in this article was to develop theological imagination as a hermeneutical device. This was done by briefly considering the concurrence in the hermeneutic contributions of three interpreters of biblical texts, with specific regard to their understanding of biblical imagination. These were Walter Brueggemann, Paul Ricoeur and Ignatius of Loyola. Their hermeneutical contributions concur in their understanding of a biblically informed imagination, and it is specifically this aspect of the concurrence of their thought that was explored. An illustration from Proverbs 14:27, which draws on the metaphor and biblical motif of the fountain or source of life, was put forward to demonstrate how the concurrence in the contributions of these biblical interpreters may influence an imaginal engagement with the text.Keywords: Old Testament; Proverbs; Hermeneutics; The fear of the Lord/Yahweh; Walter Brueggemann; Paul Ricoeur; Ignatius of Loyola; Imaginal engagement